Quantum Micro–Nano Devices Fabricated in Diamond by Femtosecond Laser and Ion Irradiation. Issue 5 (20th May 2019) - Eaton, Shane M.; Hadden, John P.; Bharadwaj, Vibhav; Forneris, Jacopo; Picollo, Federico; Bosia, Federico; Sotillo, Belen; Giakoumaki, Argyro N.; Jedrkiewicz, Ottavia; Chiappini, Andrea; Ferrari, Maurizio; Osellame, Roberto; et al.
Abstract: Diamond has attracted great interest as a quantum technology platform thanks to its optically active nitrogen vacancy (NV) center. The NV's ground state spin can be read out optically, exhibiting long spin coherence times of ≈1 ms even at ambient temperatures. In addition, the energy levels of the NV are sensitive to external fields. These properties make NVs attractive as a scalable platform for efficient nanoscale resolution sensing based on electron spins and for quantum information systems. Diamond photonics enhance optical interactions with NVs, beneficial for both quantum sensing and information. Diamond is also compelling for microfluidic applications due to its outstanding biocompatibility, with sensing functionality provided by NVs. However, it remains a significant challenge to fabricate photonics, NVs, and microfluidics in diamond. In this Progress Report, an overview is provided of ion irradiation and femtosecond laser writing, two promising fabrication methods for diamond‐based quantum technological devices. The unique capabilities of both techniques are described, and the most important fabrication results of color center, optical waveguide, and microfluidics in diamond are reported, with an emphasis on integrated devices aiming toward high performance quantum sensors and quantum information systems of tomorrow. Abstract : Diamond's nitrogen vacancy (NV) optically active color center is an ideal candidate for a qubit with long spin coherence times and room temperature operation. This report provides an overview of the latest progress of ion irradiation and femtosecond laser fabrication of photonics and microfluidics in diamond for interfacing with NVs, for high‐performance quantum sensors and quantum information systems.